Agricultural Digitalization and Strengthening Farmer Capacity through an Agricultural Website and AgriTech Workshop in Gumeng Village, Jenawi District, Karanganyar Regency - Wijayanti, Desna Ayu; Pamastutiningtyas, Terrensia Sekar; Wiyoga, Ajietama Imam; Safitri, Anggita Ghina; Aksani, Nasrin; Wulandari, Pitri; Febriana, Annisa Alfi; Irawan, Erwin; Boi, Jumiati Sulaika (Pascasarjana Universitas Mataram, 2025)
This community service activity was conducted in collaboration with the Muhammadiyah University of Karanganyar's Real Work Lecture (KKN) activities and KKN Group 13 in Gumeng Village, Jenawi District, Karanganyar Regency. The purpose of the activity is to support the development of local potential through agricultural digitalization and capacity building for farmers. The main program includes the launch of the Desa Gumeng agricultural website as a promotional and educational medium, as well as the organization of the